2016
DOI: 10.1111/petr.12875
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus DNA monitoring in serum and whole blood in pediatric liver transplant recipients who do or do not discontinue immunosuppressive therapy

Abstract: The rate of PTLD can be reduced by weaned IS guided by monitoring of EBV DNA. In this single-center retrospective case series study, we analyzed how reduction in IS influenced EBV DNA levels in whole blood and serum in 30 children during the first year after liver transplantation, and how these levels were related to symptoms putatively due to EBV. Primary and reactivated EBV infection was seen in 18 (60%) and eight patients (27%), respectively. Thirteen patients (42%) developed chronic high load the first yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…In this month's Pediatric Transplantation, Kullberg-Lindh et al report a study of 30 pediatric liver recipients between 2003 and 2012, examining the dynamics of EBV viral loads after transplantation 6. Consistent with prior reports, the authors found a high rate of EBV donor/recipient mismatch (67%) and measurable EBV viral loads post-transplant, with 87% of recipients having at least one episode in their first year.…”
mentioning
confidence: 66%
“…In this month's Pediatric Transplantation, Kullberg-Lindh et al report a study of 30 pediatric liver recipients between 2003 and 2012, examining the dynamics of EBV viral loads after transplantation 6. Consistent with prior reports, the authors found a high rate of EBV donor/recipient mismatch (67%) and measurable EBV viral loads post-transplant, with 87% of recipients having at least one episode in their first year.…”
mentioning
confidence: 66%
“…6 Moreover, persistent EBV infection is often observed in children who received transplantation not only of liver, but also of heart and kidney. 4,9 Our previous study identified the risk factors for CHEBV load carriage: long warm ischemic time, high GRWR, and preoperative EBV seronegativity. 5 However, there are no reported studies on how CHEBV impacts the liver graft, even though EBV is one of the viruses that causes hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Regarding therapy for EBV DNAemia, it has been reported that antivirals did not prevent EBV infection or chronic high-load carriage; moreover, reduction/discontinuation of immunosuppressants (IS) might not also improve persistent EBV DNAemia. 4 In any case, close serial monitoring of EBV DNA is considered useful for early diagnosis and prevention of PTLD and EBV-related diseases. [6][7][8] Although EBV is one virus that cause hepatitis (infectious mononucleosis), most pediatric recipients with chronic high EBV loads (CHEBV) are asymptomatic and the high viral load resolves spontaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apenas um paciente apresentou rejeição aguda, 1,5 meses após suspensão da medicação. A retirada total da imunossupressão resultou em uma redução do número de cópias de EBV em sangue periférico, porém os oito pacientes mantiveram replicação viral mesmo após 2 anos ou mais da suspensão55 .Com um mecanismo de ação diferente dos inibidores da calcineurina, por inibição da via de mTOR (mammalian target of rapamycin), o Sirolimus constitui uma opção terapêutica para pacientes que se recuperam de uma PTLD. Seus efeitos antiproliferativos contra doenças malignas56 , decorrem de demonstrações in vitro da parada na progressão do ciclo celular e da indução de apoptose57 .…”
unclassified